Kinetic studies on thermal degradation of natural rubber/butyl rubber - Muhammad Sholeh; ihda Novia Indrajati; Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2018)
The knowledge of how rubber breakdown on heating in oxidative environment is important in processing and using the material. In the present work, we performed thermogravimetric analysis and utilized three iso-conversional kinetic models to get apparent activation energies of thermal degradation of natural rubber/butyl rubber. Blending of RSS/butyl and additives was done using a laboratory two-roll mill. Cure time of the blended compound was determined by a moving die rheometer. The compound was compression moulded at 160°C with a pressure of 150 kg/cm2 using a laboratory hot press. Thermogravimetric analysis was carried out from 30°C to 800°C in air flow of 200 ml/min with heating rates of 5, 10, 15, and 20°C/min. The kinetic parameters were determined by three isoconversional models (Kissinger, Doyle, and Flynn–Wall–Ozawa model). The result revealed that the thermal decomposition of the blend occurs in two stages, DTG peaks tends to shift to a higher temperature and the values of DTG peaks increase with the increase of heating rate, and the three isoconversional models gave similar apparent activation energies. The activation energy obtained can be used to predict thermal lifetime of the material.